Akuntan Publik: Kewenangan Menghitung Kerugian Keuangan Negara Tindak Pidana Korupsi - Hidayatullah, Hidayatullah; Triono, Agus; Sumarja, FX (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The rise of corruption in Indonesia has caused losses to state finances. There were 1,261 cases of corruption from 2004 to 3 January 2022, with state losses in 2021 reaching IDR 62.9 trillion and in 2020 with a total loss of IDR 56.7 trillion. Seeing this phenomenon, researchers conducted research on whether public accountants can calculate state financial losses using a theory of authority approach with a normative research methodology. The study results show that there are practically no laws and regulations which state that a Public Accountant has the authority to calculate State Financial Losses unless assigned by the BPK and the Attorney General's Office. The authority to audit state finances can be carried out by several state institutions such as the BPKP, KPK and BPKP, but the authority to calculate state finances based on laws and regulations is still the authority of the Indonesian Financial Audit Agency (BPK RI).